2016
DOI: 10.1515/labmed-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Einführung des deutschlandweiten Neugeborenenscreenings für Mukoviszidose

Abstract: ZusammenfassungDie Mukoviszidose oder Cystische Fibrose (CF) ist eine autosomal rezessiv vererbte Stoffwechselerkrankung und mit einer regional schwankenden Inzidenz von ca. 1:3.300–1:5.800 eine der häufigsten angeborenen Stoffwechselerkrankungen in Deutschland. Durch eine mutationsbedingte verminderte oder fehlende Funktion von Chloridkanälen kommt es hier zu einer Veränderung der Sekretzusammensetzung aller exokrinen Drüsen. Die mittlere Lebenserwartung von Mukoviszidose-Patienten konnte durch verbesserte Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…As the first study to review the literature for information around HSU in CF, we have identified the small number of studies that focus their attention on deriving HSU data for CF patients for the health states that may be needed to model the cost effectiveness of interventions for CF. Considering the improvements in CF mortality and morbidity over the last 50 years, which are largely related to improvements in screening [41,42] and treatment of the condition [1,43], this finding comes as a surprise, especially since health economic models currently exist that examine the cost effectiveness of a range of interventions available to CF patients [15,40,[44][45][46][47][48]. For this dearth of evidence to come to light at this time suggests that CF research around health utilities has been slow.…”
Section: Discussionmentioning
confidence: 99%
“…As the first study to review the literature for information around HSU in CF, we have identified the small number of studies that focus their attention on deriving HSU data for CF patients for the health states that may be needed to model the cost effectiveness of interventions for CF. Considering the improvements in CF mortality and morbidity over the last 50 years, which are largely related to improvements in screening [41,42] and treatment of the condition [1,43], this finding comes as a surprise, especially since health economic models currently exist that examine the cost effectiveness of a range of interventions available to CF patients [15,40,[44][45][46][47][48]. For this dearth of evidence to come to light at this time suggests that CF research around health utilities has been slow.…”
Section: Discussionmentioning
confidence: 99%